(untitled) (Applied Biological Research, 2016)
Thirty-one local germplasm lines of Brassica rapa var. yellow sarson, collected from eastern parts of Uttar Pradesh (India) were evaluated along with two commercial varieties as checks in two environmental conditions (timely sown E1 and late sown E2 conditions). Data collected on 14 morphological characters was subjected to D2 statistics. The 31 germplasm lines were classified into 8 and 12 clusters under E1 and E2, respectively.InE1, cluster I had a maximum of 15 genotypes while cluster III, VII and VIII had only one genotype each, in E2, cluster III had maximum of 15 genotypes whereas cluster IV, V, VII, VIII, X, XI, and XII had only one genotype each. Likewise, the inter-cluster average D2- value was maximum (26.81) between cluster III and VIII and minimum between cluster V and I (2.80). Intra-cluster average D2 values ranged from 0.00 to 4.63. In late sown condition, the inter-cluster distance was maximum between IV and II (51.93) and minimum in cluster VI and IX (4.965). Intra-cluster average D2 value ranged from 0.0 to 4.594. The genotypes which occupied distant clusters can be used in hybridization programme as parents to recover more heterotic hybrids. Secondary branchesplant-1,glucosinolatecontent, seed yield, seeds siliqua-1, primary branches plant-1 and siliqua length contributed maximum towards total divergence in timely sown condition whereas secondary branches plant-1, seed yield, primary branches plant-1, glucosinolate content, and main raceme length were the major contributors in late sown conditions.